ANALISIS STRATEGI PENJUALAN PRODUK COCOA BUTTER PURWOKERTO MENGGUNAKAN PENDEKATAN MODEL AIDA - Fathah Rezki Putranto; Panca Wahyu Ahmadi; Yuliawan Sulistyo Wibowo; Mohammad Fahrenza; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the marketing communication strategy of Cocoa Butter Bakery in Purwokerto using the AIDA model (Attention, Interest, Desire, Action). The research is motivated by the increasing competition in the local culinary business sector and the need for micro, small, and medium enterprises (MSMEs) to optimize digital marketing in order to enhance brand awareness and sales performance. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The research subjects consisted of the business owner, employees, and customers of Cocoa Butter, while the research object focused on the sales and marketing communication strategies implemented. The findings indicate that Cocoa Butter has applied all stages of the AIDA model; however, the level of effectiveness is not evenly distributed across each stage. The Attention and Action stages require further strengthening, particularly through the use of digital advertising, interactive content, and online sales promotions. Meanwhile, product quality, customer experience, and attractive visual presentation serve as key strengths in the Interest and Desire stages. This study concludes that the AIDA model provides a comprehensive framework for evaluating marketing effectiveness and can serve as a basis for developing more integrated and sustainable digital marketing strategies for local culinary businesses.